ANALISIS BAURAN PEMASARAN KAFE LEKRA CIANJUR DALAM UPAYA MENINGKATKAN PENJUALAN - sulaeman, pradika (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2021)
Lekra Cafe is one of the cafes in Cianjur, It is known that sales have decreased from time to time. For this reason, researchers are interested in conducting research on Lekra Cafe Marketing Mix Analysis in an Effort to Increase Sales. This study uses the theory of Philip Kotler and Armstrong on the marketing mix parameters and Basu Swastha for the sales parameters. This study uses a qualitative method by using in-depth interview data collection techniques to the manager of the Lekra cafe. The data analysis technique used is SWOT analysis according to Freddy Rangkuti. In this study, the informants are the managers of the Lekra cafe as the object of interviews and data of sales from time to time and the customers of the Lekra cafe consumers who have purchased as the object of the interview are flexible. The results of the study can be concluded that the Lekra cafe is in the Quadrant I position, meaning that it has an internal strength of 2.96; weakness 2.67; odds 2.02; and has a threat of 2.4. So as to produce a point coordinates x = 0.29; y= 0.7. This shows that the coordinates are in Quadrant I, which supports an aggressive strategy. Where this aggressive strategy shows a very profitable position, that Lekra cafe has opportunities and strengths so that it can optimally take advantage of existing opportunities and is on the right track by continuing to carry out aggressive development strategies that can increase sales. The strategy that must be applied in this condition is Growth Oriented Strategy.